Outcomes of descemet stripping automated endothelial keratoplasty for pediatric descemet membrane detachment with diffuse corneal edema - Ben, Hanzhi; Xiao, Gege; Zhang, Pei; Peng, Rongmei; Xie, Zijun; Hong, Jing (Frontiers in Pediatrics, 2025)
PurposeTo report Descemet stripping automated endothelial keratoplasty (DSAEK) outcomes for pediatric Descemet membrane detachment (DMD) with diffuse corneal edema.MethodsThis study included seven cases of pediatric DMD presented at Peking University Third Hospital during October 2017 and April 2022. The collected data included patient demographics, etiology, configuration of the DMD, preoperative and postoperative vision and central corneal pachymetry, surgical outcomes, and complications.ResultsThe mean age of the children was 3.27 ± 4.73 (range: 0.33–13) years old. Etiologies included cataract surgeries, glaucoma surgeries, and forceps-related injuries. In all cases, the central areas of the corneas were involved. Three patients had received Descemetopexy at first but failed. DSAEK was successfully performed in all eyes. Compared to the preoperative visual acuity (LogMAR 2.57 ± 0.23), postoperative visual acuity (LogMAR 0.78 ± 0.25) was significantly improved (P < 0.01). Postoperative central corneal pachymetry measured within a month after DSAEK (850 ± 163 μm) showed satisfactory improvement when compared to the preoperative one (1,304 ± 234 μm, P = 0.005). Early postoperative complications included graft dislocation in one case and was successfully managed with air bubbling.ConclusionPediatric DMD might suffer a lower success rate of Descemetopexy due to the anatomical peculiarity. Reconstructing visual pathway to promote early visual development justifies more aggressive treatment like DSAEK, which has demonstrated satisfactory results.